RUMORS AND THEIR ECONOMIC IMPACTS - Molouk Kenawy, Dr. Ezzat (IJRDO - Journal of Business Management, 2016)
The economic field is considered as the most affected field of rumors due to all its issues. Such issues include those of subside, taxation, salaries, wages, rising of exchange rates, stock markets, foreign investment, etc. A rumor appears in order to realize an economic purpose or illegal profit. Lack of confidence between the public and the government is one of the main reasons behind the spread of rumors. The research aims to identify concept, characteristics and conditions necessary for rumors success. It aims as well to identify the reasons, motives and means of rumors spread. The research aims also includes identification of rumors types and sources while displaying some examples and models of the most important rumors which have been recently launched and had negative effects on the national economy particularly the subsequent consequences of launched and spread rumors on the financial market, exchange rates and their impacts on the economic growth, foreign investment and national production. Realizing the research aims, the analytical and descriptive approach was adopted through the description of various rumors spread phenomenon .The research consists of six main parts in additional to an introduction